Green synthesis in nanomedicine and human health - Glover, Richard L. K.; Nyanganyura, Daniel; Mulaudzi, Rofhiwa Bridget; Mufamadi, Maluta Steven (Boca Raton, FL : CRC Press, 2021)
Green synthesis is an emerging method for deriving nanoparticles present in natural plants for use in nanomedicine. Written by experts in the field, Green Synthesis in Nanomedicine and Human Health showcases the exciting developments of this specialty and its potential for promoting human health and well-being. This book gives practical information on novel preparation methods for identifying nanoparticles present in natural plants. It discusses applications of nanoparticles in combating communicable, non-communicable and vector-borne diseases. It also explores the potential for nanoparticles to combat antimicrobial resistance through improvements in treatment methods, diagnostics and drug delivery systems. Features scientific evidence of opportunities for integrating indigenous flora into nanomedicine to develop cost-effective therapeutic and diagnostic solutions for diseases, including cancer, tuberculosis, malaria and diabetes. Places green synthesis and nanomedicine in the African orthodox and traditional healthcare context. Provides policymakers with scientific evidence to inform policies for controlling or mitigating dangerous diseases. This book is essential reading for students, scientists, policymakers and practitioners of nanotechnology, and will appeal to anyone with an interest in integrating traditional African healthcare and Western medicine.
OCLC-licensed vendor bibliographic record.
Keywords: Nanomedicine; Nanotechnology; Biosynthesis; SCIENCE / Chemistry / General; MEDICAL / Alternative Medicine; SCIENCE / Life Sciences / Botany